A Fundamental Inequality of Algebroidal Function. (3rd December 2012) - Huo, Yingying; Sun, Daochun
Abstract : By using a new mapping of Ahlfors covering surfaces, a fundamental inequality in the angular domain for the algebroidal function is obtained.